Subcutaneous Low Molecular Weight Heparin versus Subcutaneous Unfractionated Heparin in the Treatment of Deep Vein Thrombosis: a Polish Multicenter Trial - Lopaciuk, S; Meissner, A J; Filipecki, S; Zawilska, K; Sowier, J; Ciesielski, L; Bielawiec, M; Glowinski, S; Czestochowska, E; others (Thrombosis and Haemostasis, 1992)
In a prospective multicenter trial, 149 consecutive patients with phlebographically proven proximal and/or distal deep vein thrombosis of the leg were randomly allocated to receive subcutaneously for 10 days either low molecular weight heparin CY 216 (Fraxiparine) in a fixed dose or unfractionated heparin (UFH) in doses adjusted according to the activated partial thromboplastin time. Pre- and post-treatment phlebograms were assessed blindly using the Arnesen’s score system in 134 patients available for analysis of the treatment efficacy. The mean phlebographic score after 10 days of treatment was significantly decreased in both groups (p <0.001) in comparison with the baseline score but the difference in score changes between the two groups was not statistically significant. There was an improvement in 45/ 68 patients (66%) in the Fraxiparine group and in 32/66 patients (48%) in the UFH group, and an increase in the thrombus size in 10/68 (15%) and 12/66 (18%), respectively. One symptomatic non-fatal pulmonary embolism and one major bleeding episode were observed in the UFH group. During a follow-up period of 3 months, two rethromboses had occurred in the UFH group and none in the Fraxiparine group. It is concluded that subcutaneous fixed dose Fraxiparine is safe and at least as effective as subcutaneous adjusted UFH in the treatment of deep vein thrombosis.